The Leadership Styles of the Local Universities and Colleges’ Administrators - Patricia Sonia Elardo-Zabala (International Journal of Educational Management and Development Studies, 2021)
This study determined the leadership styles of the administrators of the local universities and colleges (LUCs) in the provinces of Cavite, Laguna, Batangas, Rizal and Quezon commonly known as CALABARZON Region in the Philippines. The descriptive-evaluative method of research was used. Data were gathered using a self-constructed Likert type questionnaire from the one-hundred eleven (111) randomly selected administrators. The statistical tools applied were weighted mean, Pearson r, and single factor Analysis of Variance (ANOVA). Findings revealed that charismatic and command and control showed significant difference in the responses on leadership style practices when grouped as to provinces as contrasted with innovative, laissez-faire, pace setter, servant, and situational which showed no significant statistical difference. Though the leadership style practices of the school administrators were clearly manifested as to style, efforts may be directed to further strengthen trust since people are the lifeblood of the organization, thus, they must be valued. Also, as leaders of educational institutions, they should employ approaches that are appropriate for different sets of purposes or circumstances to further improve the relationship with the team.